The master gardener - F. Seling, Penning; Wee, Cindy; Akir, Oriah; Wan Hassan, Sharifah Zakiah; Ramakrishnan, Prabha; Pereira, Helen; Ghazali, Azlina (UiTM Sarawak, 2004)
Peter Chan is a master gardener. He left China in the mid-1960s and immigrated to Portland, Oregon, where he bought a modest ranch-style home. His garden is a masterpiece. It is filled withhundreds of different plant species—flowers, perennials, shrubs, vegetables, lawns, and fruit trees—located along beautiful paths and around sparkling pools. All have been artistically positioned and painstakingly maintained.